Healthful School Environment: A Comparative Study of Public and Private Primary Schools in Ogun State, Nigeria - Amoran OE; Kupoluyi OT; Salako AA; kupoluyi OT (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Introduction: A healthy school environment (physical, biological and socio-cultural) serves as a major determinant of health and greatly infl uences the individual's level of intellectual growth and development. This study was therefore designed to assess the school environmental health services in both private and public primary schools in Ogun state Nigeria. Methods: The study was a comparative cross-sectional survey of Private and Public Primary Schools in Ogun state, Nigeria conducted between February and May, 2014 in Ogun State, Nigeria using a ultistage sampling technique. Participants in the study were interviewed using a structured questionnaire, which was administered by a trained interviewer. Data collected was analyzed using the SPSS version 20.0. Results: A total of 360 head teachers served as respondents for the study. Dust bins and waste paper baskets were available in 58 (32.2%) Public Schools and 123 (68.3%) Private Schools (X2= 46.946,P= 0.001). About half, 90 (50.0%) and 97 (53.9%) in Public and Private Schools respectively use a bore hole or a mono pump as their source of water supply and 14 (7.8%) Public Schools and 30 (16.7%) Private Schools make use of well water (X2= 33, P= 0.001). A ratio of 1 toilet to greater than 90 pupils was owever observed in 58 (32.2%) and 29 (16.1%) Public and Private Schools respectively (X2= 39.283, P= 0.001). 81% of the Schools in this study practiced open dumping/ burning as their method of waste disposal with the Public Schools more than the Private Schools, 162 (90.0%) Public Schools and 128 (71.1%) Private Schools (X2= 46.22, P= 0.001). Ventilation was adequate in 81% of the schools and controllable in 71%. Students were sitting on the fl oor in 27% of the schools in the study population. Conclusion: The study shows that the environmental health situation in Nigerian schools is poor. There is the need for patrol teams to inspect and monitor the activities of the schools in Nigeria and other developing countries. Security has become a major issue in school health care.